2006
DOI: 10.1093/her/cyl113
|View full text |Cite
|
Sign up to set email alerts
|

Infant-feeding attitudes of expectant mothers in Northern Ireland

Abstract: Northern Ireland (NI) has one of the lowest rates of breast-feeding initiation and duration in both the UK and the industrialized world. This study therefore aimed to explore the relationship between infant-feeding attitudes and feeding intention and outcome in expectant mothers within NI. Expectant mothers (n 5 200) were recruited from hospital antenatal booking clinics. Each completed a demographic questionnaire and the self-administered Iowa Infant Feeding Attitude Scale (IIFAS). Participants (n 5 192) were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

11
85
2
4

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(102 citation statements)
references
References 17 publications
11
85
2
4
Order By: Relevance
“…This finding consistent with studies done in United States (Persad & Mensinger, 2008), United Kingdom (Shaker, Scott, & Reid, 2004), Ireland (Sittlington, Stewart-Knox, Wright, Bradbury, & Scott, 2007), Canada (Twells et al, 2014) and Korea (Kang, Choi, Hyun, & Lee, 2015) who found that breastfeeding intention is associated with positive breastfeeding attitudes.…”
Section: Discussionsupporting
confidence: 92%
“…This finding consistent with studies done in United States (Persad & Mensinger, 2008), United Kingdom (Shaker, Scott, & Reid, 2004), Ireland (Sittlington, Stewart-Knox, Wright, Bradbury, & Scott, 2007), Canada (Twells et al, 2014) and Korea (Kang, Choi, Hyun, & Lee, 2015) who found that breastfeeding intention is associated with positive breastfeeding attitudes.…”
Section: Discussionsupporting
confidence: 92%
“…Also, although it was explained that participation in the study would not affect services received in the clinic, results could be more positive toward breastfeeding because participants were giving socially acceptable answers. 19 However, if participants were truly reacting to the environment and survey, we would have expected even higher mean composite scores than observed. Also, in creating a total IIFAS score, each question is treated equally, and it is possible that some items may have more predictive value than others.…”
Section: Discussionmentioning
confidence: 85%
“…[13][14][15][16][17][18][19][20][21] In Scotland, Scott et al 17 and Shaker et al 18 administered the IIFAS to a sample of low-income expectant women and their partners and found it to be valid in predicting feeding choice. The IIFAS also was found to have acceptable reliability and validity in its Croatian, Romanian, and Chinese translations.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The IIFAS has been tested with various populations, such as postpartum women, health visitors, fathers, pregnant women, and university students. The psychometric data from reliability studies indicated that the IIFAS of Cronbach's ␣ ranges from .79 in Northern Ireland (Sittlington, Stewart-Knox, Wright, Bradbury, & Scott, 2007) to .86 in the United States (De La Mora & Russell, 1999) and .89 in Scotland (Dungy et al, 2008). The IIFAS shows that it is predictive of the choice of infant feeding methods as measured by behavioral intention, and it is also predictive of the actual feeding behavior as measured by the duration of breastfeeding.…”
Section: Methodsmentioning
confidence: 99%